INTERELASI ANTARA BAHASA DAN PIKIRAN - Jazeri, M. (Pusat Pengembangan Bahasa IAIN Tulungagung, 2011)
The relation of language and thought can be viewed from two sides. Firts, language is viewed as a medium to express perception, thinking, ideas, and emotion. This perspective believes that thought influences language. Second, language influences thought, with the sense that men are only be able to think, perceive, and feel because of the presence of language. This perspective believes that language has an subjective orientation to describe the world and men?s experiences. This subjecive orientation which further shapes how men think and speak a language. As the result, two different people having different languages will think and speak differently. So, language and thought have a reciprocal relationship in which language influences thought and thought influences language. The first view is called the instrumentalism, while the second is called determinism.